2019
DOI: 10.1177/1352458519864928
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 IgG seropositivity is associated with worse visual outcomes after optic neuritis than MOG-IgG seropositivity and multiple sclerosis, independent of macular ganglion cell layer thinning

Abstract: Background: Comparative studies of characteristics of optic neuritis (ON) associated with myelin oligodendrocyte glycoprotein-IgG (MOG-ON) and aquaporin-4-IgG (AQP4-ON) seropositivity are limited. Objective: To compare visual and optical coherence tomography (OCT) measures following AQP4-ON, MOG-ON, and multiple sclerosis associated ON (MS-ON). Methods: In this cross-sectional study, 48 AQP4-ON, 16 MOG-ON, 40 MS-ON, and 31 healthy control participants underwent monocular letter-acuity assessment and spectral-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 41 publications
(52 reference statements)
9
63
0
1
Order By: Relevance
“…Interestingly, and in line with our prior observations ( 8 ), we found that, despite a similar severity of pRNFL and GCIPL thinning in AQP4-ON and MOG-ON, visual outcomes clearly diverged between these two entities, with MOG-ON eyes having relatively preserved visual acuity, whereas AQP4-ON eyes experienced markedly worse visual outcomes compared to both MOG-ON and MS-ON. The biological underpinnings of this observation remain unclear.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, and in line with our prior observations ( 8 ), we found that, despite a similar severity of pRNFL and GCIPL thinning in AQP4-ON and MOG-ON, visual outcomes clearly diverged between these two entities, with MOG-ON eyes having relatively preserved visual acuity, whereas AQP4-ON eyes experienced markedly worse visual outcomes compared to both MOG-ON and MS-ON. The biological underpinnings of this observation remain unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Of these, 202 articles were selected and assessed for eligibility at the full-text level. After careful evaluation, 35 studies were included that met the inclusion criteria ( 8 , 29 , 30 , 33 , 36 , 39 , 41 , 45 , 47 , 48 , 51 – 54 , 57 , 59 , 63 , 65 , 66 , 68 , 69 , 71 , 72 , 74 85 ). The detailed flow chart is presented in Supplementary Figure 9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Optic neuritis is commonly associated with multiple sclerosis (MS); however, bilateral optic neuritis is unusual in adult-onset MS, and inflammatory relapses are uncommon in people with MS aged over 60 years. By contrast, NMO does manifest with bilateral optic neuritis, and with inflammatory relapses in older people; however, NMO-related optic neuritis is usually severe, with marked visual impairment and incomplete recovery 1. Anti-myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease is a strong possibility as it frequently presents with recurrent optic neuritis and good recovery after attacks 2.…”
Section: Question 1: What Is the Differential Diagnosis?mentioning
confidence: 99%